2018
DOI: 10.1177/0963662518801170
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, cultural cognition, and media effects: Worldviews drive news selectivity, biased processing, and polarized attitudes

Abstract: According to cultural cognition theory, individuals hold opinions about politically contested issues like climate change that are consistent with their “cultural way of life,” conforming their opinions to how they think society should be organized and to what they perceive are the attitudes of their cultural peers. Yet despite dozens of cultural cognition studies, none have directly examined the role of the news media in facilitating these differential interpretations. To address this gap, drawing on a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 51 publications
(54 reference statements)
2
45
0
Order By: Relevance
“…In everyday situations, both motivational influences and failures in uncertainty-guided information search can lead to biased or inaccurate beliefs, albeit via distinct mechanisms. For example, a person who does not believe in climate change is likely to show a preference for media that refutes its occurrence (19), reinforcing preexisting beliefs. Alternatively, people with doubts about the science of global warming (20) might fail to act on this uncertainty, and as a consequence not seek out further, potentially corrective evidence.…”
mentioning
confidence: 99%
“…In everyday situations, both motivational influences and failures in uncertainty-guided information search can lead to biased or inaccurate beliefs, albeit via distinct mechanisms. For example, a person who does not believe in climate change is likely to show a preference for media that refutes its occurrence (19), reinforcing preexisting beliefs. Alternatively, people with doubts about the science of global warming (20) might fail to act on this uncertainty, and as a consequence not seek out further, potentially corrective evidence.…”
mentioning
confidence: 99%
“…A huge body of literature explores how climate change coverage is used, perceived, interpreted, and negotiated (Nisbet 2018). Empirical studies have been conducted in different countries-with a clear bias towards European and US audiences-but the relevance of spatial factors for mediated communication about climate change has not been systematically addressed by communication scholars.…”
Section: State Of Researchmentioning
confidence: 99%
“…Media play a central role in bringing climate change to people's homes-via TV, newspaper, radio, or social networks. This role should be explored in order to better understand climate-related attitudes (Newman, Nisbet, and Nisbet 2018;Taddicken 2013;Brulle, Carmichael, and Jenkins 2012;Arlt, Hoppe, and Wolling 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that public attitudes of Americans toward scientific facts are now shaped by individuals' worldviews and exposure to right-or left-leaning media (Newman, Nisbet, & Nisbet, 2018) as well as their partisanship and religiosity (Pasek, 2018). US conservatives in particular are distrustful of social scientists who they believe carry out a liberal agenda (Cofnas, Carl, & Woodley of Meine, 2017).…”
Section: Public Representationmentioning
confidence: 99%